Challenges in innovation in halal product development: understanding the hurdles - Bakar, Jamilah (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Interest and awareness in halal food products have grown tremendously over the years; however, the ability to produce innovative products such as ingredients or replacing a functional ingredient in existing products is still a big challenge. Mass production and convincing the manufacturer to adopt the innovative product is undeniably difficult. Therefore, this paper is an attempt to examine and share some experiences starting from developing the idea to the bench work, filing of patent and eventually possible commercialization.